(untitled) (Bulletin KNOB, 2000)
From the preceding it will be clear that an 8th-century dating for the Heilig- Kruiskapel at Domplein in Utrecht cannot be maintained. All dating methods used to date the Heilig-Kruiskapel point to a period after the middle of the 8th century at the earliest. In view of the 14C calibration, the stratigraphy of the wallwork and the ground-levels connected with this, a dating in the 10th century, preferably at the end of it, is most likely. Consequently, it may be concluded that the 10th-century dating for the Heilig-Kruiskapel ascertained by A.E. van Giffen in the thirties of the 20th-century is still correct according to the data known at present. There are a few indications for the individual dating of the southern arm of the cross of the chapel, like one 14C calibration, that it concerns a 7th-century cella here.